Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 7.1 Participatory Disease Surveillance (PDS)―Overview - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
Participatory disease surveillance explores knowledge of local livestock keepers and veterinarians to identify diseases in the study area.